PENDIDIKAN UNTUK KEWIRAUSAHAAN DAN PENGABDIAN KEPADA MASYARAKAT - Yusnah, Yusnah; Darwati, Endang (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Education for entrepreneurship and community service in Indonesia varies greatly with the aim of creating entrepreneurship. Entrepreneurship education began to be programmed by various organizations, both organizations in the fields of primary, secondary and higher education, as well as government and private organizations. Through this movement it is hoped that entrepreneurial culture can become part of the work ethic of the Indonesian people and nation, which in turn can be born new entrepreneurs who are reliable, resilient and independent. The purpose of this article is to develop an understanding of the importance of entrepreneurship education as a form of community service. The growing interest in entrepreneurship found in young souls who are now getting bigger with all the risks that will be accepted, that is the burden that will be borne by entrepreneurs, and the failure of the worst dreams that always overshadow entrepreneurs. This article concludes that entrepreneurship education in tertiary institutions is needed in any field regardless of the area occupied or one's profession.Keywords— Education, entrepreneurship, community. Abstrak— Pendidikan untuk kewirausahaan dan pengabdian kepada masyarakat di Indonesia sangat bervariasi yang bertujuan untuk menciptakan wirausaha. Pendidikan kewirausahaan mulai diprogramkan oleh berbagai organisasi, baik organisasi bidang pendidikan dasar, menengah dan pendidikan tinggi, serta organisasi pemerintah dan swasta. Melalui gerakan ini diharapkan budaya kewirausahaan dapat menjadi bagian etos kerja masyarakat dan bangsa Indonesia, yang pada akhirnya dapat dilahirkan wirausaha-wirausaha baru yang handal, tangguh dan mandiri. Tujuan artikel ini adalah mengembangkan pemahaman tentang pentingnya pendidikan kewirausahaan sebagai bentuk pengabdian kepada masyarakat. Tumbuhnya minat berwirausaha yang terdapat pada jiwa-jiwa muda yang sekarang semakin besar dengan segala resiko yang akan diterima, itulah beban yang akan ditanggung oleh wirausaha, dan kegagalan mimpi paling terburuk yang selalu membayangi para wirausahawan. Artikel ini menyimpulkan bahwa pendidikan kewirausahaan di perguruan tinggi diperlukan dalam bidang apapun tanpa memperhatikan bidang yang ditekuni atau profesi seseorang.Kata kunci— Pendidikan, wirausaha, masyarakat.